Silica-Supported Dichlorophosphate Catalyzed Beckmann Rearrangement and Dehydration of Oximes Under Microwave Irradiation - Li, Zheng; Lu, Zhong (Letters in Organic Chemistry, 2008)
Silica-supported dichlorophosphate had been proved to be an efficient, recoverable and reusable catalyst for Beckmann rearrangement of a variety of ketoximes and dehydration of various aldoximes in THF under microwave irradiation. This protocol has advantages of high conversion, high selectivity, short reaction time, no environmental pollution and simple work-up procedure.
Keywords: oxime